Synthesis and Application of CaO-MgO Catalyst from Dolomite for Biodiesel Production - Vikky Pramudya Herdiansyah Poeloengan; Ananda Melati Octa Pratama; Erwan Adi Saputro (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Dependence on dwindling fossil fuels drives the development of biodiesel as a renewable alternative energy. However, the use of homogeneous catalysts, which are difficult to separate, non-reusable, and generate waste, remains a major obstacle. This review aims to examine the potential of dolomite-based heterogeneous catalysts (CaO–MgO) as a more sustainable solution. These catalysts are synthesized through the calcination of dolomite, an abundant carbonate mineral with main components of CaCO₃ and MgCO₃, and can be modified by adding Fe₂O₃, Fe₃O₄, SiO₂, or Na doping to enhance catalytic activity, surface area, and bifunctional properties. Various vegetable oil feedstocks such as Crude Palm Oil (CPO), used cooking oil, tamanu oil, and canola oil have been successfully converted into biodiesel via transesterification (and simultaneous esterification-transesterification) using these catalysts, yielding biodiesel >90% with quality that meets national and international standards. Thus, the synthesis of CaO–MgO catalysts from dolomite promises an effective, economical, and environmentally friendly application for large-scale biodiesel production.